The Welfare Needs of the Elderly in Lat Krabang District, Bangkok - นุชอุดม เฉลิมพล; รชตวัฒนกุล สุวัจ; รชตวัฒนกุล สนใจ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This quantitative research aimed to 1) study the level of social welfare needs of the elderly in Lat Krabang District, Bangkok, and 2) study the basic problems of the elderly that affect their social welfare needs in Lat Krabang District, Bangkok. The sample group consisted of 395 individuals aged 60 years and older in Lat Krabang District, Bangkok, calculated using Yamane’s sample size formula. The questionnaire had a reliability coefficient of 0.976. Data was analyzed using statistical software, including frequency, mean, standard deviation, and multiple regression analysis. The research results are as follows: 1. The level of social welfare needs of the elderly in Lat Krabang District, Bangkok, was found to be at the highest level overall. When considering each aspect, the respondents’ need for social welfare for the elderly was highest, followed by safety of life and property, followed by health and hygiene, housing (at the highest level), poverty and disadvantage alleviation, recreation, and education, respectively. 2. The basic problems of the elderly that affect their social welfare needs in Lat Krabang District, Bangkok, The hypothesis testing on how basic problems of the elderly affect their need for social welfare in Lat Krabang District, Bangkok, revealed that basic problems such as health problems, mental health problems, and economic problems significantly impacted their need for social welfare in Lat Krabang District, Bangkok, at a statistical significance level of .01. Recommendations to researchers and the government include providing free healthcare for the elderly and organizing activities to transfer vocational knowledge and traditional wisdom from the elderly.